The European Union: A Model for Economic Cooperation (Journal of Asian Development Studies, 2026)
Since its origins in the aftermath of the Second World War, the European integration project has evolved from sectoral cooperation into an advanced system of economic, monetary, and increasingly participatory governance. The European Union (EU) represents a unique form of regional integration that transcends traditional trade arrangements, combining supranational authority with intergovernmental decision-making (Bickerton et al., 2015; De Grauwe, 2020). This paper critically examines the EU as both an economic and an emerging deliberative system. It explores the historical foundations of integration, the Union's institutional structure, and the public goods it generates, particularly through the single market and the euro. Furthermore, the study situates the EU within contemporary debates on democratic legitimacy by analysing recent participatory innovations, especially the Conference on the Future of Europe and its European Citizens’ Panels. It argues that while the EU has achieved unparalleled success in economic integration, its long-term sustainability depends on strengthening democratic legitimacy through deliberative mechanisms and citizen participation. The paper focuses on the fact that the EU remains the most advanced model of regional integration globally, yet its future lies in reconciling economic governance with participatory democracy and policy responsiveness.